Chemical composition and metabolizable energy values of corn germ meal obtained by wet milling for layers - Albuquerque,CS (2014)
An experiment was carried out to determine the chemical composition, metabolizable energy values, and coefficients of nutrient digestibility of corn germ meal for layers. The chemical composition of corn germ meal was determined, and then a metabolism assay was performed to determine its apparent metabolizable energy (AME) and apparent metabolizable energy corrected for nitrogen (AMEn) values and its dry matter and gross energy apparent metabolizability coefficients (CAMDM and CAMGE, respectively). In the 8-day assay (four days of adaptation and four days of total excreta collection), 60 29-week-old white Lohman LSL layers were used. A completely randomized experimental design, with three treatments with five replicates of four birds each, was applied. Treatments consisted of a reference diet and two test diets, containing 20 or 30% corn germ meal. Results were submitted to analysis of variance and means were compared by the Tukey tests at 5% probability level. The chemical composition of corn germ meal was: 96.39% dry matter, 49.48% ether extract, 1.87% ashes, 7243 kcal gross energy/kg, 11.48% protein, 0.19% methionine, 0.21% cystine, 0.48% lysine, 0.40% threonine, 0.72% arginine, 0.35% isoleucine, 0.83% leucine, 0.57% valine, and 0.37% histidine, on as-fed basis. There were no statistical differences in AME, AMEn, CAMDM, and CAMGE values with the inclusion of 20 and 30% corn germ meal in the diets. On dry matter basis, AME, AMEn, CAMDM, and CAMGE values of corn germ meal were: 4,578 and 4,548 kcal/kg, 4,723 and 4,372 kcal/kg, 64.95 and 61.86%, respectively.